Medijski repertoarji in diskurzivne skupnosti - Luthar, Breda (Teorija in praksa, 2015)
Due to radical changes in media consumption, manifested in the widespread mediatization and proliferation of the uses of personal media in everyday life, research about media audiences can no longer focus on a single medium. In order to identify ideal-typical combinations of media platforms and aesthetic cultures in the population of the two largest Slovenian cities, the concept of media repertoires was used. The study shows that the media consumption of our respondents is structured into four typical media repertoires: the digital elite, digital natives, television viewers and newspaper readers. These four repertoires represent also distinct socio-cultural formations. In social terms, digital audiences therefore do not constitute a homogenous social community, but should be understood as class-differentiated discursive cultures or "meaning systems".
Keywords: Audiences; Digital media; diskurzivne skupnosti; Elektronski mediji; Mass media; Množični mediji; Občinstvo; potrošnja; Slovenia; Slovenija